Analyses Of Sustainability Performance And Financial Performance (A Comparative Study Pt Astra Agro Lestari Tbk And Pt Dharma Satya Nusantara Tbk In The 2021-2023 Period) - Eleonora, Luisa; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze and compare the sustainability performance and financial performance of PT Astra Agro Lestari Tbk. and PT Dharma Satya Nusantara Tbk through qualitative descriptive analysis and content analysis. The data was harvested via document studies on the sustainability reports and annual reports of both companies in the 2021-2023 period. This study finds that PT Astra Agro Lestari Tbk. and PT Dharma Satya Nusantara Tbk. Limitedly applied and disclosed GRI standards in 2021 and partially applied the standards in 2022 and 2023. Further, both companies had suboptimal financial performance during the research period, as seen from the declining trends of their liquidity and activity ratios. Their market ratios also tended to be overvalued, and their profitability ratios indicated earnings margin decline. However, both companies recorded satisfactory solvency ratios as they had succeeded in reducing their liabilities.